KAJIAN SEMIOTIKA PESAN IKLAN ROKOK LA LIGHTS “KENALI LUAR DALAM” DALAM PROSES KOMUNIKASI HAROLD LASSWELL - Gabriela Thesalonica Efendy; Peni Pratiwi; Michael Bezaleel Wenas (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2025)
Indonesian goverment has established prohibiting policy direct visualization of cigarette products in advertisments, as a result cigarette companies must convey their advertisements implicitly, as exemplified in LA Lights commercial titled, “Kenali Luar Dalam #MikirDulu”. This study aims to analyze the meaning behind the LA Lights advertisement using qualitative research method, Harold Lasswell’s communication theory, and semiotic analysis theories from Saussure and Barthes. Through message analysis (‘what if’), true meaning of both visual an verbal signs within the advertisement revealed. The research subjects consist of young adults aged 21-25 who are either university students or part-time employee, have smoking habit, and technologically adaptive. In conclusion, the fundamental meaning of this advertisement is that the LA Lights “Kenali Luar Dalam #MikirDulu” commercial seeks to encourage audiences not only to percieve the advertisement as a promotional strategy but also to cultivate critical and wise thinking in understanding various aspects of daily life.